The Role Of The Teacher In Developing The Character Of Individual Worship In Early Children - Alfiah, Siti; Kristiana, Dian; Rusdiani, Nurtina Irsad (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2025)
The aim of this research is to determine the role of teachers in cultivating the character of diligent worship in early childhood at PAUD Tunas Harapan, Sukorejo village, Puhpelem subdistrict, Wonogiri district. This research uses a qualitative approach with descriptive methods. Data collection using observation, interviews and documentation methods. The research results show that the formation of the character of diligent worship in early childhood cannot be separated from the role of the teacher, including: 1. The role of the teacher as a facilitator, namely the teacher provides an example as an example, namely the teacher arrives on time, the teacher gives an example when praying with good etiquette, provides an example in carrying out learning activities from start to finish. 2. The teacher acts as an inspirer, a teacher must be able to raise the enthusiasm of students by telling the story of Rosululloh and his companions to inspire students. 3. The teacher acts as a motivator, namely providing motivation to appreciate students who complete assignments well, giving rewards to children who excel, giving gifts and words of praise so that children are motivated to be enthusiastic about learning. 4. The teacher as a dynamist, namely the teacher has a view and attempts to build the character of students and has high creativity in finding a solution to every problem faced by students. 5. Teacher as evaluators have a role as people who carry out evaluations in learning at school. Evaluation in learning has an important role so that teachers know to what extent students have understood what the teacher/teacher has conveyed. Of the several roles teachers have carried out, the aim is to shape students at PAUD Tunas Harapan, Sukorejo village, Puhpelem sub-district into children who are diligent in worshiping, such as being accustomed to praying before doing assignments in class, accustomed to praying before and after eating, willing to learn to pray with joy, learning to perform ablution happily, accustomed to  coming to the mosque, willing to learn to memorize short letters happily and knowing the letters. hijaiyah with pleasure. All of this is instilled or developed as early as possible in early childhood because these are the fundamental religious teachings of every individual, community, nation and state's life.